2018
DOI: 10.1016/j.pnpbp.2017.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Regional gray matter volume and structural network strength in somatic vs. non-somatic delusional disorders

Abstract: The data support the notion that dysfunctional somatosensory and peripersonal networks could mediate somatic delusions in patients with DI in contrast to delusional disorders without somatic content. The data also suggest putative content-specific neural signatures in delusional disorders and in delusion formation per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
(53 reference statements)
1
17
0
Order By: Relevance
“…Another structural imaging study of patients with SZ and somatic delusions has also shown structural abnormalities in frontal, insular and thalamic regions [35]. As discussed previously, alterations in those regions support the notion of impaired neural networks related to somatosensory perception and top-down regulation of sensory input, i. e. prediction processing [34]. Thus, impaired somatosensory networks could mediate somatic delusions as opposed to delusions without somatic content.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Another structural imaging study of patients with SZ and somatic delusions has also shown structural abnormalities in frontal, insular and thalamic regions [35]. As discussed previously, alterations in those regions support the notion of impaired neural networks related to somatosensory perception and top-down regulation of sensory input, i. e. prediction processing [34]. Thus, impaired somatosensory networks could mediate somatic delusions as opposed to delusions without somatic content.…”
Section: Introductionsupporting
confidence: 53%
“…To elucidate possible neural substrates of somatic delusions, we previously investigated structural brain alterations in patients with DI, using magnetic resonance imaging (MRI) and voxel-based as well as source-based morphometry techniques. In two studies, we compared patients with DI to healthy controls (HC) [32,33], and recently, we compared patients with DI to HC and to patients presenting with non-somatic DD (NS-DD) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a deficit of integrative visual areas, particularly the retrosplenial cortex, was suspected in delusional misidentification [27]. In support of a content-specific neural signature of delusional belief, we have previously shown abnormal brain structure of cortical and subcortical sensorimotor regions in patients with somatic type delusions [23,24,32].…”
Section: Introductionmentioning
confidence: 75%
“…A model proposed by Palaniyappan and Liddle [28] suggests disrupted reciprocal connectivity of the PFC to the insula to precisely distribute representations of goal-directed and planned behavior. Of note, abnormal insula volume has been also observed in patients with somatic type DD [23,100]; thus, this particular brain area is not among the regions that specifically mediate delusional content.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation